Politik dan Strategi Budaya Etnik dalam Pilkada Serentak di Kalimantan Barat - Kristianus Kristianus (Politik Indonesia: Indonesian Political Science Review)
The local politics in West Kalimantan thick politically charged ethnic identity. Local political politically involved two ethnic identity which is a native of West Kalimantan, namely ethnic Dayak and Malay. The state of the two ethnic rivalry is becoming more open in the era of district autonomy that is triggered by direct local elections. This competition occurs because history records that the ruling ethnic elite running ethnic hegemony over other ethnic groups. Regional head election (PILKADA) is currently running. Of the seven districts in West Kalimantan which organizes PILKADA very apparent that they are oriented to capture the voice ethnicity. Ethnic identity became a political commodity since this issue most easily sold to seize the people's voice. This paper use the incorporation of the views that are instrumentalism and internal colonialism perspective . The author has the view, that perspective instrumentalism able to see how an elite play social identity and cultural group to gain power and view of internal colonialism that saw socio-economic disparities and discrimination as the root of the strengthening of solidarity groups. This view is helpful to explain the fanaticism ethnic factor as a cultural strategy that occurred in the present and why identity politics in West Kalimantan is an inherent part of the local politics of this period.